Stories of Muhammed Saadoon Al Sebahi: Artistic Study in his collection (Fog as Sun) - Hadeed Ressen, Lect. Dr. Salam (Basra studies journal, 2022)
The Iraqi story-teller Muhammed Saadoon AL-Sebahi is one of the third generation of the story –tellers in Iraq. In his stories, he made it easy to use the Modern Empiricism Concepts of story –telling into the old story-telling styles, and vice versa. This study tries to handle one of this story -teller's creative Lectures, and that is his collection of stories called: "Sun Like Fog", which is deliberately chosen, because it presents the story-teller's developmental narrating style. It is hoped for this study to accomplish its aim.